Research on Continuous Wave Electromagnetic Effect in Swept Frequency Radar. (31st December 2021) - Du, Xue; Wei, Guanghui; Zhao, Hongze; Pan, Xiaodong
Abstract : In order to establish the prediction model of radar equipment in multisource complex electromagnetic environment, the blocking effect and false alarm interference effect caused by single-frequency CW (continuous wave) electromagnetic interference on typical radar equipment are studied. Taking a certain sweep radar as the research object, the equivalent injection test of EMI (electromagnetic interference) is carried out. Based on the theory of radar front door coupling, the interference mechanism of EMI to radar receiver RF front end is revealed, and the variation law of blocking target and false alarm target level is analyzed. The results show that, under the single-frequency CW-EMI, the target echo level decreases with the increase of the interference field strength, and the false alarm level increases with the increase of the interference field strength. The blocking jamming sensitive bandwidth is about f 0 ± 200   MHz, and the false alarm jamming sensitive bandwidth is about f 0 ± 80   MHz .